Origins, Loss, and Recovery in Patrick Modiano's Voyage de noces and Dora Bruder - Ann L. Murphy (Studies in 20th & 21st Century Literature, 2005)
By alluding to the writing of his 1990 novel Voyage de noces in the course of the narration of 1997 Dora Bruder, author Patrick Modiano invites an examination of the connections between these two works. This paper demonstrates how Voyage de noces and Dora Bruder, when studied together as a sort of diptych, are informed by what commentators have described as Modiano's simultaneous preoccupations with the expression of absence and loss, on the one hand, and with the use of writing to compensate for these, on the other. Specifically, a formal and thematic relationship between these two texts is shaped first by a movement from origins to loss, as developed in Voyage de noces, and then by an inverse movement from loss to recovery as outlined in Dora Bruder. However, just as the fullness of being that typically characterizes the idealized version of origins—here, meaningful parental presence and a sense of personal identity—is always already deflated by the recognition that this fullness is not a given but rather remains to be realized, absolute recovery, too, is impossible.
Keywords: Voyage de noces; Patrick Modiano; Dora Bruder; French Literature; diptych; absence and loss; absence; loss; origins; writing; recovery; identity; personal identity; parent; parental presence